Induction of Epstein-Barr virus nuclear antigen and DNA synthesis in a human epithelial cell line after Epstein-Barr virus infection. - Ben-Bassat, H (1982)
The association of Epstein-Barr virus (EBV) with nasopharyngeal carcinoma is supported by the presence of EBV genomes in the epithelial elements of the tumor and by elevated antibody titers to EBV-specific antigens in the patients; the levels of these titers are related to the clinical course of the disease. However, since most laboratory data suggest that EBV is a B-lymphotropic virus, it is unclear how the virus becomes associated with the epithelial elements of the nasopharynx. The purpose of the present work was to find a human model system to study this association. A human epithelial line (U) was found that could be directly infected by EBV, and viral functions, the induction of EBV nuclear antigen and cellular DNA synthesis, were demonstrated. The U line was established in 1957 by the late H. J. Van Kooten (Kok-Doorschodt at the University of Utrecht), and although it is no longer diploid, it exhibits density inhibition. When U cells were infected with EBV, EBV nuclear antigen was expressed in 6 to 16% of the cells, 1 and 2 days after infection with B95-8 virus, but not with the P3HR-1 strain. No evidence for virus replication was obtained; immunofluorescence staining for early antigens and virus capsid antigens gave negative results. Quantitative adsorption experiments for EBV indicated that the adsorption capacity of U cells is significant (60% of Raji cells). The present results also demonstrated that infection with the virus overcomes block(s) in cellular DNA synthesis caused by 5-fluorodeoxyuridine. The induction of DNA synthesis was determined by increased incorporation of [3H]thymidine into the cells. The highest level of isotope incorporation was observed at about 15 h after infection and thereafter decreased. Analysis of the induced DNA indicated that it was of cellular origin.